Enabling Human Development through Poshan Abhiyaan: A Situation Analysis - Mobar Roy, Sonal (International Journal of Psychosocial Rehabilitation, 2024)
Ensuring healthy lives and promoting the well-being at all ages is essential to achieve sustainable development as entailed in SDG 3. With this as the roadmap, the government of India has launched the Poshan Abhiyaan (National Nutrition Mission) to improve nutritional outcomes for children, pregnant women, lactating mothers and adolescent girls. Conceptualized as a Jan Andolan or ‘people’s actions’ for promoting inclusive participation, it aims at reaching every household with the message of nutrition. The author examines the implementation of the program as an agency and the enhancement of human development thus envisioned through Sen’s Capability Approach